Politicization of bureaucracy: the idea of strengthening ASN neutrality - Sihaloho, Nahot Tua Parlindungan; Herlan (Research and Development Agency Ministry of Home Affairs, 2020)
According to a State Civil Apparatus Commission (KASN) report in 2019, more than 200 State Civil Apparatus (ASN) violated neutrality in the general elections and local elections during the 2015-2018 period. Based on a preliminary study, it found that several violations had occurred because of a dilemma for the State Civil Apparatus (ASN) concerned. State Civil Apparatus (ASN) must be neutral by the law mandate, but they cannot be impartial if they want their career as State Civil Apparatus (ASN) not to be damaged. This study uses a normative legal research method with a literature study research design. This study seeks to examine the effects of bureaucratic politicization and find win-win solutions to the problems experienced by the State Civil Apparatus (ASN). The results of this study emphasize the need to expand the authority of the State Civil Apparatus Commission (KASN) to impose sanctions on violators of neutrality. The implications of this research are the following six practical recommendations: first, the existing rules after the enactment of Law No. 5/2014 must be revised so that Civil Service Officer (PPK) was no longer given position to politicians, but rather the senior State Civil Apparatus (ASN); secondly, election criminal law enforcement does not need to involve the police, and the prosecutor's office (just General Election Supervisory Agency); third, localization of the State Civil Apparatus Commission (KASN) by establishing a State Civil Apparatus Commission (KASN) in the regions to increase the effectiveness of the oversight function of the State Civil Apparatus (ASN); fourth, the length of service for officials is only one term; fifth, the abolition of voting rights for State Civil Apparatus (ASN); sixth, changing the career guideline model of the State Civil Apparatus (ASN) from regional government autonomy to the central government by the rank or class.